APLIKASI PEMBELAJARAN BERBASIS ANDROID PADA MATERI SISTEM PERIODIK UNSUR UNTUK PENINGKATAN PEMAHAMAN KONSEP MAHASISWA - Pahriah, Pahriah; Khery, Yusran (Hydrogen: Jurnal Kependidikan Kimia, 2017)
This article describe the development result of android base self learning aplication to help students reach conceptual understanding on elements periodic siystem. In form research and development, it was carred out by ADDIE model. Subject of this research is chemisry education students of IKIP Mataram who fulfill Elementary Chemistry I lectur. Based on research it was concluded that : (1) android base mobile learning media application on elements periodic system subject material was produce and operate successly wity adobe air application support.  Content and design validity of this product are 81.11 % and 83.97 % successively with very aligible category. Practiotioner and small group trial subject respond are 80.83 % and 89.02 % with very eleigible cathegory; (2) this android base application was enhance students elements periodic system conceptual understanding effectively. It was proved by N-gain average of students conceptual understanding enhancment is 0.82 with high category and t-gain value (6.135) larger than ttable(tα = 0.55; dk= 9  = 2.62).